The Seasonal Water Balance of Western-Juniper-Dominated and Big-Sagebrush-Dominated Watersheds - Nicole Durfee; Carlos G. Ochoa (Hydrology, 2021)
The combined impacts of woody plant encroachment and climate variability have the potential to alter the water balance in many sagebrush steppe ecosystems in the Western USA, leading to reduced water availability in these already water-scarce regions. This study compared the water-balance characteristics of two adjacent semiarid watersheds in central Oregon, USA: one dominated by big sagebrush and one dominated by western juniper. Precipitation, springflow, streamflow, shallow groundwater levels, and soil moisture were measured. The potential evapotranspiration was calculated using the Hargreaves–Samani method. Potential evapotranspiration and a water-balance approach were used to calculate seasonal actual evapotranspiration. The shallow aquifer recharge was calculated using the Water-Table-Fluctuation-Method. Evapotranspiration, followed by deep percolation, accounted for the largest portion (83% to 86% of annual precipitation) of water output for both watersheds. Springflow and streamflow rates were generally greater at the sagebrush-dominated watershed. Snow-dominated years showed greater amounts of groundwater recharge and deep percolation than years where a larger portion of precipitation fell as rain, even when total annual precipitation amounts were similar. This study’s results highlight the role of vegetation dynamics, such as juniper encroachment, and seasonal precipitation characteristics, on water availability in semiarid rangeland ecosystems.